2016
DOI: 10.9734/acri/2016/30587
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oils from the Leaves, Seeds, Seed-pods and Stems of Bixa orellana L. (Bixaceae)

Abstract: Aims: The aim of the present study is to report the volatile compounds identified in the essential oils obtained by hydrodistillation from the various parts of B. orellana. Study Design: The design includes the extraction of essential oil from air-dried leaves, seeds, seed-pods and stems samples of B. orellana and the determination and identification of the chemical constituents of the oils. Place and Duration of Study: Mature leaves, seeds, seed-pods and stems of B. orellana were collected along LASU-Isheri R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Discordant results were found by Giwa-Ajeniya et al [47], who verified in EO samples of B. orellana leaves, from Nigeria, higher α-guaiene contents (49.3%), together with guaiol (8.1%), valenceno (7.7%) and β-elemeno (5.9%). As well as Silva et al [66] under study with the EO of the roots.…”
Section: Toxicity Of Eossupporting
confidence: 50%
See 1 more Smart Citation
“…Discordant results were found by Giwa-Ajeniya et al [47], who verified in EO samples of B. orellana leaves, from Nigeria, higher α-guaiene contents (49.3%), together with guaiol (8.1%), valenceno (7.7%) and β-elemeno (5.9%). As well as Silva et al [66] under study with the EO of the roots.…”
Section: Toxicity Of Eossupporting
confidence: 50%
“…In relation to the yield of the EO obtained from the leaves dried at 45 °C, according to what was also reported by Souza et al [30] the grinding facilitated the extraction, because it exposed the structures that contained the EO to the process and increased the contact surface of the leaves with the water used hydrodistillation. Giwa-Ajeniya et al [47] found similar results when they evaluated the yield of EO through hydrodistillation of B. orellana leaves in the Alimosho area, Lagos State, Nigeria.…”
Section: Physicochemical Parameters Of Eosmentioning
confidence: 71%
“…According to previous reports of the chemical composition of the EO of B. orellana leaves, Lawrence et al in 1973 reported ishwarane (54%) a sesquiterpene hydrocarbon (C 15 H 24 ) as the main compound [ 26 ], while Zollo et al in 1998 identified ishwarane (43.5%), guaiol (7.3%) and γ-murolene (6.2%) [ 27 ]. More recently, Giwa-Ajeniya et al in 2016 identified twenty-one volatile compounds for B. orellana leaves from Nigeria, where the main compounds were SH α-guaiene (49.3%, CF: C 15 H 24 ), guaiol (8.1%), valencene (7.7%) and β-elemene (5.9%) [ 28 ]. Oliveira et al in 2020 reported isocaryophyllene (26.58%, CF: C 15 H 24 ), 1R-α-pinene (19.49%) and β-pinene (12.04%) as the main components for fresh B. orellana leaves collected in Brazil [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This operation was done by searching the keywords, “ Bixa orellana ” and “reported compounds”. From different articles, we found 172 compounds [supplementary file S1 ] proclaimed from different parts of the B. orellana [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. To identify potential neurological effects against the GABA A receptor, those compounds were chosen for in silico screening.…”
Section: Methodsmentioning
confidence: 99%